Numerical Analysis of Mhd Dusty Fluid Flow Over Stretching Sheet in A Porous Medium - Goh, Jun Shen; Noorzehan Fazahiyah Bt. Md Shab, (Enhanced Knowledge in Sciences and Technology, 2022)
The purpose of this research is to study the effects of magnetohydrodynamic dusty fluid flow over stretching sheet in a porous medium. A mathematical model has been done to simulate a steady, incompressible, two-dimensional MHD flow of electrically conducting dusty fluid over a stretching sheet in a porous medium. The partial differential equations of the model are reduced to ordinary differential equations by similarity transformation. The system of reduced ordinary differential equations is solved by bvp4c method in MATLAB software. The effects of the governing parameters on the velocity distribution and temperature distribution are demonstrated graphically while the skin friction coefficient and temperature gradient are also calculated and displayed in tabular form. The governing parameters that have been investigated are permeability parameter, magnetic parameter, thermal conductivity variation parameter, and slip parameter. The results show that each parameter will have the different ways to affect the process.